APPLICATION OF POSYANDU GEOGRAPHIC INFORMATION SYSTEM OF PINANG SUB-DISTRICT USING LEAFLET-BASED IGNITER CODE - Didi Kurnaedi; Ilham Setiawan; Haryanto Haryanto; Erna Oktora (Jurnal TAM (Technology Acceptance Model), 2020)
The development of information technology now has reached to all fields and become something very important in life, humans need information that is fast, accurate, and accurate in presenting data. A geographical information system an information processing service that contains data information displayed in a map view, this system can provide information more easily and support health management. Posyandu geographic information systems can help communities to find out where a posyandu is located. Designing a leaflet-based geographical information system on posyandu in Pinang District to search for posyandu located in the Pinang District area of Tangerang City. The results of this study are in the form of a geographic information system that is connected to a google map that can show a map of the location of the community health center and information from each Posyandu in Pinang District, Tangerang City.